Carbon ion radiation therapy for high-risk meningiomas - Combs, Stephanie; Hartmann, Christian; Nikoghosyan, Anna; Jäkel, Oliver; Karger, Christian; Haberer, Thomas; Deimling, Andreas von; Münter, Marc; Huber, Peter E.; Debus, Jürgen; Schulz-Ertner, Daniela (Radiotherapy and oncology, 2010)
BACKGROUND: We analyzed outcome after a carbon ion boost in combination with precision photon radiation therapy in patients with meningiomas. - PATIENTS AND METHODS: Ten patients with meningiomas were treated with carbon ion RT as part of a Phase I/II trial. Carbon ion RT was conducted in conjunction with fractionated stereotactic RT (FSRT) or intensity-modulated RT (IMRT). Eight patients were treated as primary RT, in 2 patients carbon ion RT was performed as re-irradiation. Carbon ion RT was applied with a median dose of 18 GyE, and photon RT was applied with a median dose of 50.4 Gy. Two patients with a history of former irradiation received 18GyE of carbon ion RT and a reduced dose of photon treatment. - RESULTS: The median follow-up time was 77 months. Five patients died during follow-up, of which four died of tumor progression. In the group treated in the primary situation, actuarial survival rates after RT were 75% and 63% at 5 and 7 years. After re-irradiation, both patients died at 10 and 67 months, respectively. Actuarial local control rates after primary RT were 86% and 72% at 5 and 7 years. Two patients developed tumor recurrence after re-irradiation, 6 and 67 months after treatment. - CONCLUSION: In conclusion, carbon ion radiation shows promising results in patients with atypical or anaplastic meningiomas. Further evaluation in a larger, prospective study in comparison to proton RT or modern photon RT is needed to corroborate these results.